Efectos del uso de estrategias participativas en la comprensión lectora de los estudiantes de 5° de básica primaria (2019)
The general objective of this research work is to determine the effects of the use of participatory strategies to improve reading comprehension in 5th grade students at the district school light. The essence of this proposal is to identify the effect of collaborative work on reading comprehension in order to develop such skills in students. This research has a positivist paradigm, with an empirical-inductive epistemological approach, a quantitative research approach, quasi-experimental design. The total primary basic population of The Light's BDI consists of 380 students, and the sample consists of 41 fifth graders. to which the instruments used in this case pre and post test were applied, validated by three experts, and subsequently make the intervention which consisted in the application of ten teaching sequences based on the application participatory strategies to strengthen reading comprehension in the population under study.